Development Potential of Bali Cattle in Baito Sub-district South Konawe Regency - Musram Abadi; Restu Libriani; La Ode Nafiu; Hairil H Hadini; Abdul Rizal; G. Gerhana; S. Surahmanto (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2023)
This study aims to analyze the development potential of Bali cattle in the Baito District, South Konawe Regency. Respondents in this study were Balinese cattle breeders in Baito District, South Konawe Regency. Determination of respondents in this study was carried out by purposive sampling with a total of 80 respondents so that each village/sub-district was represented by 10 breeders with the criterion of breeders having ≥ 3 Bali cattle. The research variables observed were technical aspects and non-technical aspects. Data analysis used in this study is descriptive analysis, to describe the condition of Bali cattle farms in the Baito District area. The results stated that Baito District of South Konawe Regency has the potential as a Bali cattle development area based on the parameters of the age of productive breeders and the experience of breeders is long enough, semi-intensive maintenance systems and breeding maintenance patterns, normal reproductive activity, types and sources of feed available, and adequate livestock officers, and facilities and infrastructure available.